A Click‐Chemistry Linked 2′3′‐cGAMP Analogue. Issue 8 (17th January 2019) - Dialer, Clemens Reto; Stazzoni, Samuele; Drexler, David Jan; Müller, Felix Moritz; Veth, Simon; Pichler, Alexander; Okamura, Hidenori; Witte, Gregor; Hopfner, Karl‐Peter; Carell, Thomas
Abstract: 2′3′‐cGAMP is an uncanonical cyclic dinucleotide where one A and one G base are connected via a 3′‐5′ and a unique 2′‐5′ linkage. The molecule is produced by the cyclase cGAS in response to cytosolic DNA binding. cGAMP activates STING and hence one of the most powerful pathways of innate immunity. cGAMP analogues with uncharged linkages that feature better cellular penetrability are currently highly desired. Here, the synthesis of a cGAMP analogue with one amide and one triazole linkage is reported. The molecule is best prepared via a first Cu I ‐catalyzed click reaction, which establishes the triazole, while the cyclization is achieved by macrolactamization. Abstract : 2′3′‐cGAMP is an uncanonical cyclic dinucleotide which consists of one A and one G nucleobase connected via a 3′‐5′ and a unique 2′‐5′ phosphodiester linkage. Here, we report a convergent synthesis of a cGAMP analogue with one amide and one triazole replacing the natural phosphodiester backbone. The molecule is best prepared by a first CuAAC reaction followed by macrolactamization.